2010
DOI: 10.1007/s10897-010-9306-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Family Experiences and Opinions on Adding 22q11 Deletion Syndrome to the Newborn Screen

Abstract: 22q11 deletion syndrome (22qDS) has recently been proposed for addition to the newborn screening panel in Wisconsin and it seems likely that it may soon be considered in other states as well. Input from patients with 22qDS and their family was gathered from 21 phone interviews. Cardiac, palate, hypocalcemia, and multiple anomalies were common reasons for involved patients to be diagnosed, though age at diagnosis ranged from birth to adulthood. Many commented on their struggles with 22qDS, including worries abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 7 publications
(11 reference statements)
2
34
0
Order By: Relevance
“…Thirteen studies revealed negative and positive emotions experienced amongst families, caregivers, and patients (Bales et al, 2010a; Briegel et al, 2008; Chan et al, 2015; Costain et al, 2012; Goodwin, Alam, et al, 2017; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Hercher & Bruenner, 2008; Karas et al, 2014; Klingberg et al, 2010; Okashah et al, 2015; Phillips et al, 2017; Reilly et al, 2015). Three subthemes were identified: emotions experienced by parents and caregivers, emotional experiences faced by siblings, shared emotional experiences.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies revealed negative and positive emotions experienced amongst families, caregivers, and patients (Bales et al, 2010a; Briegel et al, 2008; Chan et al, 2015; Costain et al, 2012; Goodwin, Alam, et al, 2017; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Hercher & Bruenner, 2008; Karas et al, 2014; Klingberg et al, 2010; Okashah et al, 2015; Phillips et al, 2017; Reilly et al, 2015). Three subthemes were identified: emotions experienced by parents and caregivers, emotional experiences faced by siblings, shared emotional experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were qualitative in nature (Bales et al, 2010a; Goodwin, Alam, et al, 2017; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Klingberg et al, 2010; Phillips et al, 2017), seven used mixed methods (Butcher et al, 2012; Chan et al, 2015; Cohen et al, 2017; Hercher & Bruenner, 2008; Karas et al, 2014; Martin et al, 2012; Okashah et al, 2015), and two exclusively quantitative papers were included (Briegel et al, 2008; Reilly et al, 2015). Qualitative methods used included interviews, surveys, and questionnaires.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations